Effet antioxydant et antifongique de la spiruline « Arthrospira platensis » - ALOUACH, Hasna; BOUMEDIENE, Abderrahmene (My University, 2024)
The objective of the study is to verify the antioxidant properties of spirulina and to test its antifungal activity against pathogenic strains to evaluate its potential as an antifungal agent. The materials used in the spirulina study included pathogenic fungal strains from the LMBAFS laboratory at Abdelhamid Ibn Badis University in Mostaganem and Arthrospira Platensis spirulina from the Al Kiram farm. The experimental methods included the preparation of methanol extract of spirulina, the determination of total polyphenols and total flavonoids by colorimetric methods, the measurement of antioxidant power using the DPPH test, and the evaluation of antifungal activity by the AWDT well diffusion method. The results and discussions of the spirulina study showed that this microalgae has antioxidant and antifungal properties. Analyses revealed a high content of total flavonoids compared to total polyphenols, as well as strong radical scavenging power. Antifungal activity was observed against the yeast C. albicans, but not against Aspergillus brasiliensis. These results highlight the multiple benefits of spirulina as an antioxidant, antifungal, and antimicrobial agent, reinforcing its interest in various fields such as nutrition and health. In summary, the study on spirulina confirmed its antioxidant and antifungal properties, highlighting its potential as a beneficial superfood for health. These results strengthen the interest in spirulina as a dietary supplement and natural therapeutic agent.
Keywords: Spirulina; microalgae; antioxidant; antifungal; Arthrospira Platensis